Perhaps the stars - Palmer, Ada (Palmer, Ada. Terra Ignota, 2021)
"From the 2017 John W. Campbell Award Winner for Best Writer, Ada Palmer's Perhaps the Stars is the final book of the Hugo Award-shortlisted Terra Ignota series..."--